1993
DOI: 10.3109/10409239309085137
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Biochemistry and Molecular Genetics of Sulfate Activation

Abstract: This article is an overview of current research in the area of sulfate activation. Emphasis is placed on presenting unresolved issues in an appropriate context for critical evaluation by the reader. The energetics of sulfate activation is reevaluated in light of recent findings that demonstrate that the synthesis of activated sulfate is thermodynamically driven by GTP hydrolysis. The structural and functional bases of this GTPase activation are discussed in detail. The bonding and hydrolysis of the high-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 124 publications
0
99
0
Order By: Relevance
“…Earlier kinetic studies showed that cytosolic STs catalyze sequential transfer reactions with the formation of a ternary complex between enzyme, PAPS, and acceptor substrate (30,31). Whether the reaction proceeds through a Bi Bi or ordered mechanism remains controversial.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Earlier kinetic studies showed that cytosolic STs catalyze sequential transfer reactions with the formation of a ternary complex between enzyme, PAPS, and acceptor substrate (30,31). Whether the reaction proceeds through a Bi Bi or ordered mechanism remains controversial.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…cysJ and cysI encode, respectively, the flavoprotein and haemoprotein of a sulphite reductase (NADPH), whereas cysH encodes a PAPS reductase. Both the cysDNC and the cysJIH operons are required for cysteine synthesis (Leyh, 1993). The similarities to the E. coli genes suggest that the Xoo raxP, raxQ and xcysJ, xcysI and xcysH also encode components of a sulphur assimilation pathway.…”
mentioning
confidence: 95%
“…Sulphation requires the presence of the activated sulphate form PAPS, an important intermediate of the sulphate assimilation pathway in all organisms (Leyh, 1993 the adenosine-5¢-phosphoryl moiety of ATP to sulphate to form APS (adenosine-5¢-phosphosulphate). Secondly, APS kinase (ATP:adenylysulphate-3¢-phosphotransferase, EC 2.7.1.25) phosphorylates APS to form PAPS (3¢-phosphoadenosine-5¢-phosphosulphate).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many hormones, neurotransmitters, carbohydrates, and drugs are included in this pathway (Leyh 1993). PAPSS2 and SLC26A2 are expressed ubiquitously in systemic organs (Hastbacka et al 1994;Xu et al 2000).…”
Section: Haplotype Analysismentioning
confidence: 99%